Effect of Contour Cultivation on Rainfall-Runoff Relationship and Productivity in Rainfed Agriculture - Taley, S M (Journal of Agricultural Engineering, 2011)
A field experiment was carried out to test the suitability of contour cultivation with vegetative contour hedges (T2, leucaena and T3, vetivar) over cultivation across (T4) and along (T1, traditional) the slope in controlling runoff, soil and nutrient losses. During the study period of 9 years, data pertaining to surface runoff, soil and nutrient losses revealed the superiority of contour cultivations along with the vegetative hedges in controlling runoff and soil nutrient losses over cultivation across and along the slope. The average percentage runoff for the rainfall causing runoff (437.41 mm) was 14.98 (T3), 20.42 (T2), 22.46 (T4) and 28.93 (T1) along with the soil loss of 1.36 (T3), 2.31 (T2), 3.99 (T4) and 7.21 (T1) t.ha?Â¹. Maximum reduction in NPK (55 to 63%) was observed in contour cultivation along with the vetiver hedge (T3). The average yield levels of sorghum enhanced by 14.40 to 19.38% in contour cultivation with vegetative hedges (T2 and T3) and 7.45% in cultivation across the slope (T4) over the traditional practice of cultivation along the slope (T1). It was observed that contour cultivation along with the vetivar hedges (T3) is effective in controlling runoff and soil and nutrient losses. The study further indicated that the best fit equations were 4th degree polynomial for all the treatments having coefficient of determinant (RÂ²) as 0.86, 0.84, 0.72 and 0.84 for T1, T2, T3 and T4 respectively.The developed rainfall-runoff relationships could be successfully used for predicting runoff.